The Level of Social Phobia and Its Relationship to Psychological and Social Adjustment among Blind and Normal Students in Jordan - Majali, Areen A. Q. Bajes Al Jadeed (Journal of Ecohumanism, 2023)
This research aimed to compare the degree of social Phobia and its relation to social adjustment between blind and sighted students in Jordan. The research also aimed to determine if there were differences between the two groups and if social Phobia could predict the levels of social adjustment. The population in this study was 200 students, comprising 100 blind and 100 sighted students in Jordanian schools. In gathering data, two standardized tools were utilized: the Social Phobia Inventory (SPIN) to quantify social anxiety levels and the Social Adjustment Scale to determine students' adjustment towards social integration and compatibility with individuals.The research outcome showed that blind students displayed higher social phobia ratings (M = 42.77, SD = 9.83) than sighted students (M = 36.59, SD = 8.22). Blind students scored much worse than their sighted peers on social adjustment according to the study results (M = 28.33, SD = 5.95 versus M = 33.16, SD = 6.38). These two effect sizes reached large measures when compared to each other (Cohen's d = 0.69 and 0.75). According to Pearson correlation results, social Phobia was strongly linked negatively to social adjustment (r = -0.613, p < .001). The analysis showed social Phobia was a major factor in determining social adjustment scores (β = -0.613, R² = 0.375, p <.001). Social Phobia occurs frequently among blind students and simultaneously presents a significant obstacle to their social adjustment, according to the research outcomes. The author examines why visually impaired students need specialized psychological and pedagogical help to improve their social integration.